2008
DOI: 10.1111/j.1365-2702.2007.02264.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of silver‐releasing dressings in the management of infected chronic wounds

Abstract: This review strengthens the case for the use of silver dressings when managing infected chronic wounds. They appear more effective and are tolerated well by patients. However, their use should be accompanied by a comprehensive wound assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 22 publications
(46 reference statements)
0
51
0
1
Order By: Relevance
“…There is conflicting evidence about the therapeutic benefits of silver dressings in wound healing: while several systematic reviews have identified positive effects, [24][25][26][27] others have failed to establish any association. 12,28,29 Many studies analysed in these reviews included endpoints relating to healing.…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting evidence about the therapeutic benefits of silver dressings in wound healing: while several systematic reviews have identified positive effects, [24][25][26][27] others have failed to establish any association. 12,28,29 Many studies analysed in these reviews included endpoints relating to healing.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of antibiotics circa World War II, the use of silver for many of these functions declined, only to be revived in the 1960s by Moyer and Fox, as described below [reviewed in 3]. Several studies failed to show benefit in overall wound healing Some studies favor use of silver-releasing foam dressing [55,60,62], whereas others show higher cost [59,61] Current data do not support routine use of silver for this application…”
Section: Historymentioning
confidence: 99%
“…The results of these studies differ widely, and a recurring theme in the relevant meta-analyses is the need for more rigorous trials before any conclusive statements can be made [54][55][56][57][58]. Because of the countless products available for the management of chronic wounds, both with and without silver, an in-depth review of each is beyond the scope of this review but can be found elsewhere [25,36,37].…”
Section: Topical Application For Ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic wounds, the major healthcare problem, were the wounds that have been stuck in any one of the wound healing phases (hemostasis, inflammation, proliferation, and remodeling) for a period of 6 weeks or more [1,2], and usually exhibit phenomena such as existence of necrotic tissues, lack of healthy granulation tissues, incomplete remodeling of extracellular matrix, incapability of epithelialization, and an interruption in wound improvement [1,3,4]. Many factors, including personal health condition (e.g., diabetes, cardiovascular defects, hepatic diseases, immunodeficiency, aging, cancers, etc.)…”
Section: Introductionmentioning
confidence: 99%